HIV-exposed infant follow-up in Mozambique: formative research findings for the design of a cluster randomized controlled trial to improve testing and ART initiation - Vieira, Lúcia (BMC Health Serv Res, 2020)
BACKGROUND: Early infant diagnosis (EID) of HIV-exposed and initiation of HIV-positive infants on anti-retroviral therapy (ART) requires a well-coordinated cascade of care. Loss-to-follow-up (LTFU) can occur at multiple steps and effective EID is impeded by human resource constraints, difficulty with patient tracking, and long waiting periods. The objective of this research was to conduct formative research to guide the development of an intervention to improve the pediatric HIV care cascade in central Mozambique. The study was conducted in Manica and Sofala Provinces where the adult HIV burden is higher than the national average. The research focused on 3 large clinics in each province, along the highly populated Beira corridor. METHODS: The research was conducted in 2014 over 3 months at six facilities and consisted of 1) patient flow mapping and collection of health systems data from postpartum, child-at-risk, and ART service registries, 2) measurement of clinic waiting times, and 3) patient and health worker focus groups. RESULTS: HIV testing and ART initiation coverage for mothers tends to be high, but EID and pediatric ART initiation are hampered by lack of patient tracking, long waiting times, and inadequate counseling to navigate the care cascade. About 76% of HIV-positive infants were LTFU and did not initiate ART. CONCLUSIONS: Effective interventions to reduce LTFU in EID and improve pediatric ART initiation should focus on patient tracking, active follow-up of defaulting patients, reduction in EID turn-around times for PCR results, and initiation of ART by nurses in child-at-risk services. TRIAL REGISTRATION: Retrospectively registered, ISRCTN67747315, July 24, 2019.